2020
DOI: 10.1111/vde.12831
|View full text |Cite
|
Sign up to set email alerts
|

Chronic progressive lymphoedema in Friesian horses: suggestive phenotype of affected horses and genome‐wide association study

Abstract: Background -Chronic progressive lymphoedema (CPL) is a disabling condition affecting various draft horse breeds, including Friesian horses. Hypothesis -The high incidence of CPL in Friesian horses suggests a genetic component and a predisposing phenotype.Animals -For the genomic study, 26 affected and 19 control horses were evaluated. Body measurements were taken from 28 affected and nine control Friesian horses.Methods and materials -Axiomâ Equine Genotyping Array with a total of 307,474 single nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…CPL has high occurrence in draft horse breeds, especially, Clydesdales, Shires, and Belgians (Cock et al, 2006a) and, recently, Friesian was included as a susceptible breed, thus suggesting genetic content for disease development (Cock et al, 2003;Affolter, 2013;Keyser et al, 2014;Affolter et al, 2020). A previous study observed minor elastin content in dermis biopsies of susceptible draft horse breeds when compared to other draft horse breeds with no previous reports of CPL, such as Percheron (Cock et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CPL has high occurrence in draft horse breeds, especially, Clydesdales, Shires, and Belgians (Cock et al, 2006a) and, recently, Friesian was included as a susceptible breed, thus suggesting genetic content for disease development (Cock et al, 2003;Affolter, 2013;Keyser et al, 2014;Affolter et al, 2020). A previous study observed minor elastin content in dermis biopsies of susceptible draft horse breeds when compared to other draft horse breeds with no previous reports of CPL, such as Percheron (Cock et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…CPL symptoms frequently begin at the age of two years; however, long hair in limb extremities of draft horses hamper early detection of disease signs and the lesions are identified when itching starts during secondary infection (bacterial or parasitic) (Affolter, 2013;Affolter et al, 2020). In the present case report the late manifestation or identification may be a consequence of intense hair coverage on distal limbs or late manifestation in males, both of which are associated with lack of knowledge about this disease in Brazil (Keyser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations